(Sebuah Perspektif UntukStudi Gender Ke Depan) - Godefridus Samderubun (SOCIETAS, 2012)
The efforts to improve gender equity and equality have been taken place for years since the struggle of R.A. Kartini. Up to present, the efforts are still in place, however, not yet gain expected results. Preservation of gender inequality can be reproduced in family, society, as well as in the country.The increasing attention to gender is forced by women conference conducted by the UN. Four paradigms are identified: 1) Women in Develoment (WID) concept that emerging researches on womwn participation in development process; 2) Gender and Development (GAD) concept in which female is related to male; 3) Women’s empowerment; 4) Gender Mainstreaming. All of these paradigms have been implemented, but the results are not as expected.This condition reflects the needs of more critical attention in the implementation. For instances by considering women heterogeneity in terms of culture, social, and economis values, and thus it is necessary to take a need assessment in individual and institution levels. Men are also needed to take participation in gender studies to avoid bias. It ia also important to carry out program of education information communication to spread the information about women programs that have been and will be conducted to improve women participation. Also, government commitment is crucial to increase gender sensitivity in public bureaucracy